Aerosols trend and characteristics on east coast of Peninsular Malaysia by integrating remote sensing and in-situ data - Salahuddin, Mohd Muzammil (2016)
The study of atmospheric aerosol is becoming more important due to its various adverse effects on human beings, the environment and the Earth’s climate. The issue of atmospheric aerosol is a great concern to Malaysia because of the rapid development and urbanization and the regional haze occurrence. There are a number of issues concerning aerosol monitoring in Malaysia because of the weaknesses of ground-based aerosol monitoring. This study aims to apply remote sensing in conjunction with ground-based data of aerosol as solutions to the weaknesses. The correlation between remote sensing and ground-based aerosol data has been found to range from 0.014 to 0.739. Furthermore, the spatial and temporal variability of aerosol is determined. Two different patterns of monthly aerosol concentrations are identified and influenced by rainfall and monsoonal seasons. Source apportionment analysis reveals urban/industrial aerosol type as the most abundant aerosol type. It is followed by aerosols from biomass burning, maritime environment and mineral sources/dust. The Principal Component Analysis (PCA) reveals only one underlying spatial pattern in aerosol concentration which explains 62.23% of the data variability. The influence of meteorological factors, based on the multiple linear regression model is significant and able to explain 7.7% of the variation of the aerosol. This study shows that remote sensing is very useful in aerosol monitoring, especially when used in conjunction with ground-based data.